The relationship between adolescent sleep duration and exposure to school bullying: the masking effect of depressive symptoms - Zeng, Rushuang; Han, Dang; Du, Wei; Wen, Jing; Zhang, Youxian; Li, Zongyu; Du, Qun; Qi, Yan; Li, Yu; He, Jia (Frontiers in Psychology, 2024)
Background: Adolescents who suffer from school bullying are often accompanied by problems such as sleep disorders and depression. However, it remains unclear how depressive symptoms and sleep assessments such as sleep duration interact in the specific mechanisms of exposure to school bullying.Objective: To understand the role of sleep duration, depressive symptoms on school bullying in adolescents and the mediating role of sleep duration in this context.Methods: A total of 1730 adolescents were selected from Xinjiang province, China by stratified cluster random sampling in 2020, and their demographic characteristics, exposure to school bullying, depressive symptoms, and sleep duration were investigated by questionnaire. Multifactorial logistics regression analyses were performed to examine the effects of sleep duration and depressive symptoms on school bullying. Furthermore, the bootstrap method was used to explore the mediating effect and masking effect of depressive symptoms between sleep duration and school bullying by PROCESS macro in SPSS 26.0.Results: A total of 16.42% of adolescents suffered from school bullying and 12.25% showed depressive symptoms. Multifactorial logistics regression analyses revealed that possible depression and depression increase the risk of exposure to school bullying compared to normal group. Sleep duration less than 8 hours and between 8 and 10 hours are protective factors for exposure to three types of school bullying relative to those who sleep more than 10 hours. Additionally, sleep duration affected exposure to school bullying through depressive symptoms (β = 0.011) and depressive symptoms masked the effect between sleep duration and exposure to school bullying with an effect of 60.17%. The masking effect remained stable after adjusting for gender, age, ethnicity, body mass index, and exercise intensity (indirect effect = -0.017, 95%CI: -0.026 to -0.009).Depressive symptoms may be a risk factor for exposure to school bullying, while moderate and inadequate sleep duration may be protective factors for exposure to all three types of school bullying simultaneously. The effect of sleep duration on adolescents' exposure to school bullying was affected by the masking effect of depressive symptoms, and appropriate sleep duration and a positive and healthy mindset were beneficial in reducing the occurrence of school bullying.